Analisis Pembentukan Istilah-Istilah Linguistik dalam Bahasa Korea dan Bahasa Indonesia - Didin Samsudin; Jayanti Megasari; Risa Triarisanti; Ashanti Widyana; Hima Ragillia Dwinanda Putri Mahendra (DBSMB, Vocational College of Universitas Gadjah Mada, 2023)
This study was conducted to fulfill the need of students to understand linguistics courses in the Korean Language Education Study Program. The student’s understanding of linguistics starts from their ability to understand the linguistic terms. This study deals with the formation of linguistic terms in Korean language compared to their formation in Indonesian language. It is necessary to analyze Indonesian terms’ formation to find their equivalent terms. It is found that Korean linguistic terms are generally changed into Indonesian as a whole. Although some terms originate from foreign languages, the majority have undergone adaptation and adjustments to be more comprehensible. In contrast, Indonesian linguistic terms are influenced by their source language. Meanwhile, Indonesian linguistic terms are influenced by the language of origin. The formation of terms is also analyzed based on the word formation process by using morphological theory to determine the formation pattern. This research may answer the function of these terms in the process of understanding linguistics lectures at the Korean Language Education Study Program, FPBS, UPI.